PINCH1 Promotes Fibroblast Migration in Extracellular Matrices and Influences Their Mechanophenotype - Mierke, Claudia Tanja; Hayn, Alexander; Fischer, Tony (Frontiers in Cell and Developmental Biology, 2022)
Cell migration performs a critical function in numerous physiological processes, including tissue homeostasis or wound healing after tissue injury, as well as pathological processes that include malignant progression of cancer. Cell migration and invasion efficiency appears to be based on the mechano-phenotype of the cytoskeleton. The cytoskeletal properties depend on internal cytoskeletal and external environmental factors. A reason for this is connections between the cell and its local matrix microenvironment, which are established by cell-matrix adhesion receptors. Upon activation, focal adhesion proteins such as PINCH1 are recruited to sites where focal adhesions form. PINCH1 specifically couples through interactions with ILK, which binds to cell-matrix receptors and the actomyosin cytoskeleton. However, the role of PINCH1 in cell mechanics regulating motility in 3D collagen matrices is still unclear. PINCH1 is thought to facilitate 3D-motility by regulating cellular mechanical properties, such as stiffness. In this study, PINCH1 wild-type and knock-out cells were examined for their ability to migrate in dense extracellular 3D-matrices. Indeed, PINCH1 wild-type cells migrated more numerously and deeper in 3D-matrices, compared to knock-out cells. Moreover, cellular deformability was determined, e.g., elastic modulus (stiffness). PINCH1 knock-out cells are more deformable (compliable) than PINCH1 wild-type cells. Migration of both PINCH1-/- cells and PINCH1fl/fl cells was decreased by Latrunculin-A inhibition of actin polymerization, suggesting that actin cytoskeletal differences are not responsible for the discrepancy in invasiveness of the two cell types. However, the mechanical phenotype of PINCH1-/- cells may be reflected by Latrunculin-A treatment of PINCH1fl/fl cells, as they exhibit resembling deformability to untreated PINCH1-/- cells. Moreover, an apparent mismatch exists between the elongation of the long axis and the contraction of the short axis between PINCH1fl/fl cells and PINCH1-/- cells following Latrunculin-A treatment. There is evidence of this indicating a shift in the proxy values for Poisson's ratio in PINCH1-/- cells compared with PINCH1fl/fl cells. This is probably attributable to modifications in cytoskeletal architecture. The non-muscle myosin-II inhibitor Blebbistatin also reduced the cell invasiveness in 3D-extracellular matrices but instead caused a stiffening of the cells. Finally, PINCH1 is apparently essential for providing cellular mechanical stiffness through the actin cytoskeleton, which regulates 3D-motility.